The changing forms and expectations of peer review - Horbach, S. P. J. M.; Halffman, W. ( Willem) (Research integrity and peer review, 2018)
The quality and integrity of the scientific literature have recently become the subject of heated debate. Due to an apparent increase in cases of scientific fraud and irreproducible research, some have claimed science to be in a state of crisis. A key concern in this debate has been the extent to which science is capable of self-regulation. Among various mechanisms, the peer review system in particular is considered an essential gatekeeper of both quality and sometimes even integrity in science. However, the allocation of responsibility for integrity to the peer review system is fairly recent and remains controversial. In addition, peer review currently comes in a wide variety of forms, developed in the expectation they can address specific problems and concerns in science publishing. At present, there is a clear need for a systematic analysis of peer review forms and the concerns underpinning them, especially considering a wave of experimentation fuelled by internet technologies and their promise to improve research integrity and reporting. We describe the emergence of current peer review forms by reviewing the scientific literature on peer review and by adding recent developments based on information from editors and publishers. We analyse the rationale for developing new review forms and discuss how they have been implemented in the current system. Finally, we give a systematisation of the range of discussed peer review forms. We pay detailed attention to the emergence of the expectation that peer review can maintain 'the integrity of science's published record', demonstrating that this leads to tensions in the academic debate about the responsibilities and abilities of the peer review system.